Increasing informal sector business, does the impact of regulatory barriers? evidence from the enterprises survey - Nofranita, Willy; Husna, Resti Fitratul; Sismen, Andres (Universitas Muhammadiyah Yogyakarta, 2024)
This study uses survey data from the 2015 World Bank Enterprises Survey of firms operating in 9 provinces in Indonesia. Barriers to doing business in Indonesia for companies are calculated and ranked, and then qualitative methods are used to complete the discussion. This study aims to provide an overview and basis for these constraints so that the central and regional governments can collaborate in making policies that can support the progress of the business world through identification and mapping out barriers to doing business in Indonesia. The aid results show that the main obstacles to doing business in Indonesia in 2015 were the practices of competitors from the informal sector, political instability, and tax rates. The results of this study indicate that since starting a business in Indonesia, firms have been faced with difficulties in obtaining permits that are not in accordance with applicable regulations. For instance, data processing results show that of the firms that apply for business licenses in Indonesia, only 51.41% obtain operating license issuance services following regulations.